2020
DOI: 10.32615/bp.2019.080
|View full text |Cite
|
Sign up to set email alerts
|

Salt tolerance of potato genetically engineered with the Atriplex canescens BADH gene

Abstract: Potato (Solanum tuberosum L.) is among the top staple foods in the world, and salinity adversely affects its yield and quality. To improve salt tolerance in potato, the present study is focused on the Agrobacterium-mediated transformation of potato by the Atriplex canescens betaine aldehyde dehydrogenase (BADH) gene driven by single, double, and triple CaMV 35S promoters. The study led first to the detection of seven lines containing the BADH gene followed by the identification of T-DNA insertions via DNA hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Potato is cultivated globally and very sensitive to salt stress, and more than 60% crop loss is caused abiotic stresses including salt (Upadhyaya et al, 2011;Xu et al, 2014;Shafi et al, 2017). To improve potato yield and quality under salt stress condition, many transgenic potato plants have been developed using different genes with different modes of action (Shafi et al, 2017;Wang et al, 2019;Ali et al, 2020). Many osmoprotectant genes like P 5 CS, mtlD, and AtBADH have been transferred to potato, which significantly improves the salt tolerance under salt stress (Karthikeyan et al, 2011;Rahnama et al, 2011;Zhang et al, 2011).…”
Section: Transgenic Vegetables For Salt Stress Tolerancementioning
confidence: 99%
“…Potato is cultivated globally and very sensitive to salt stress, and more than 60% crop loss is caused abiotic stresses including salt (Upadhyaya et al, 2011;Xu et al, 2014;Shafi et al, 2017). To improve potato yield and quality under salt stress condition, many transgenic potato plants have been developed using different genes with different modes of action (Shafi et al, 2017;Wang et al, 2019;Ali et al, 2020). Many osmoprotectant genes like P 5 CS, mtlD, and AtBADH have been transferred to potato, which significantly improves the salt tolerance under salt stress (Karthikeyan et al, 2011;Rahnama et al, 2011;Zhang et al, 2011).…”
Section: Transgenic Vegetables For Salt Stress Tolerancementioning
confidence: 99%
“…The different transgenic studies provided significant insight into transgenes in enhancing salt tolerance in potato plants by altering enzymatic activity, physiological activity, and growth parameters (Table 1). Tolerant to salinity and tolerance related to number of promoters in transgenic lines [178] Recently, clustered, regularly interspaced, short palindromic repeats (CRISPR)/CRISPRassociated protein (CRISPR/Cas) systems have been engineered and extensively employed for genome engineering purposes [179,180]. Precise genetic manipulations, using the CRISPR system, have shown unprecedented potential in generating the desired plant phenotype in several crops [181].…”
Section: Genetic Engineering Approach To Improve Salt Tolerance In Potatomentioning
confidence: 99%
“…Previous studies have shown that plants with glycine betaine deficiency exhibit a low tolerance for heat and salinity [ 31 , 32 , 33 ]. A method for introducing the BADH gene into plants with a defect in the glycine betaine pathway that reduces their salt–stress resistance, such as Arabidopsis, Ammopiptanthus nanus, maize, potato, Persian walnut, wheat, etc., has been proposed [ 34 , 35 , 36 , 37 , 38 , 39 ]. With the continuous development of transgenic plant varieties, monitoring the environment after their large-scale cultivation has received increasing attention in the past 20 years, especially insect-resistant or herbicide-tolerant crops [ 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%